Disentangling the contributions of agentic, antagonistic, and neurotic narcissism to drive for thinness and drive for muscularity. - Leonie Hater (Public Library of Science (PLoS), 2021)
Body image concerns revolving around body ideals (thin ideal, muscular ideal) are widespread among women. Whereas a stronger preoccupation with ideal physical appearance is often assumed for narcissistic women, previous empirical findings have been mixed. Following a tripartite structure of agentic, antagonistic, and neurotic narcissism facets, we reexamined whether trait narcissism predicted drive for thinness and drive for muscularity. We further explored the role of importance of appearance as a mediator and moderator of the relation between narcissism and body image concerns. Latent structural equation modeling was applied to self-report data from two independent nonclinical female samples (NSample1 = 224, NSample2 = 342). Results underlined the importance of distinguishing between narcissism facets: Neurotic (but not agentic or antagonistic) narcissism uniquely predicted drive for thinness and drive for muscularity. Importance of appearance mediated but did not robustly moderate these relations. Hence, neurotic narcissistic women (characterized by hypersensitivity, shame, and a fragile self-esteem) are particularly prone to body image concerns. This vulnerability seems partly driven by how much importance they ascribe to their appearance. Future work might build on these insights to further unravel the processes linking neurotic narcissism to body image concerns and how these can be targeted in practical interventions.